Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 4 - Integrals - 4.5 The Substitution Rule - 4.5 Exercises - Page 346: 45



Work Step by Step

To solve this integral we will use the substitution $x^2+a^2=t$ giving $dt=t'dx=(x^2+a^2)'dx=2xdx$. Now we have $xdx=\frac{1}{2}dt.$ For the bounds: $x_1=0\to t_1=0^2+a^2=a^2$ $x_2=a \to t_2=a^2+a^2=2a^2$ Now the integral becomes $$\int_{0}^ax\sqrt{x^2+a^2}dx=\frac{1}{2}\int_{a^2}^{2a^2}\sqrt{t} dt=\frac{1}{2}\int_{a^2}^{2a^2}t^\frac{1}{2}dt=\frac{1}{2}\left.\frac{t^\frac{3}{2}}{\frac{3}{2}}\right|_{t=a^2}^{t=2a^2}=\frac{1}{3}\bigg(\Big(2a^2\Big)^\frac{3}{2}-\Big(a^2\Big)^\frac{3}{2}\bigg)=\frac{1}{3}\big(2\sqrt{2}a^3-a^3\big)=\frac{1}{3}a^3(2\sqrt{2}-1).$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.